2020
DOI: 10.1021/acsnano.9b04837
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Biomaterials with Micro/Nanotechnologies for Cell Reprogramming

Abstract: Cell reprogramming is a revolutionized biotechnology that offers a powerful tool to engineer cell fate and function for regenerative medicine, disease modeling, drug discovery, and beyond. Leveraging advances in biomaterials and micro/ nanotechnologies can enhance the reprogramming performance in vitro and in vivo through the development of delivery strategies and the control of biophysical and biochemical cues. In this review, we present an overview of the state-of-the-art technologies for cell reprogramming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 276 publications
0
45
0
Order By: Relevance
“…Cell reprogramming is the newest technology that can be used in regenerative medicine or in the treatment of genetic diseases. It is known that many physical parameters such as surface topology, stiffness, and charge can influence the reprogramming process [ 200 ]. It has already been shown that a specific surface microstructure is extremely important for cell reprogramming [ 201 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Cell reprogramming is the newest technology that can be used in regenerative medicine or in the treatment of genetic diseases. It is known that many physical parameters such as surface topology, stiffness, and charge can influence the reprogramming process [ 200 ]. It has already been shown that a specific surface microstructure is extremely important for cell reprogramming [ 201 ].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“… 165 , 166 Although combining the advantages of vaccine formulations and vaccine delivery devices is promising, micro/macro-engineering still needs to develop solutions that do not require “harsh” conditions to be compatible with nanoengineered formulations. 167 Expectedly, platform technologies that can be quickly adapted to address emerging viral diseases could speed up the pace of vaccine development.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Indeed, biophysical factors are broadly involved in orchestrating morphogenesis, angiogenesis, and tissue remodeling by modulating cell function and fate. Cells can convert the biomaterial's biophysical features into intracellular biochemical signals via for example mechanosensing resulted in ultimate gene expression 123 . Therefore, the creation of specific morphologies and surface patterns along with optimization of pore size and pore morphology has been shown to influence the growth of interconnected blood vessels within the scaffold and also the degree of vascularization through the mechanisms involving the body's immune system 120,124 .…”
Section: Treatment Of Chronic Wounds Using Angiogenic Approachesmentioning
confidence: 99%
“…There are also several studies that used ECM's derivatives such as proteoglycans and their GAGs as hydrogels or bioactive molecules immobilized onto scaffolds to bind a range of growth factors, cytokines, and chemokines through their GAG chains 123,132 . Among these proteoglycans, research findings confirmed that perlecan, or heparan sulfate proteoglycan 2 (HSPG2), has major roles in tissue and organ development and wound healing by orchestrating the binding of morphogens and delivery of angiogenic factors to cells in a spatiotemporal and dynamic manner 133,134 …”
Section: Treatment Of Chronic Wounds Using Angiogenic Approachesmentioning
confidence: 99%